Development Of Rain And Scintillation Models At Ku-Sand In Southeast Asia Tropical Countries - Jit Singh, Mandeep Singh (2006)
A two year rainfall rate, attenuation and scintillation measurement was conducted in Southeast Asia Tropical countries (USM, KMITL,USP, AdMU and ITB). The data obtained are useful to investigate the impairment due to rainfall in satellite links operating in tropical and equatorial climates. The cumulative distributions of rainfall rate, attenuation and scintillation derived from the measured data are presented and compared with those obtained with existing prediction models. Existing model for prediction of slant-path have not shown good agreement with available experimental data, confirming the need of suitable models for tropical region. Results were analysed in order to understand the potentials and the limits of each prediction model. Based on the limitations of the existing models, 1-minute rainfall rate and attenuation prediction model was developed from the knowledge of the ground point rainfall rate and attenuation cumulative distribution representative of the area where the earth station is located. Comparison between predicted and experimental results has shown significant improvements in terms of reduced prediction error over existing models. The proposed models were also used for prediction against the measured data from different location such as Brazil, Singapore and Papua New Guinea. The proposed model gave a good representation of cumulative distribution with an overall low rms for measurement sites and the three different locations mentioned above. The agreement with the measured data was found to be mainly dependent on the proper parameterization of the proposed models to the radiometeorological variables along the satellite link. Therefore, it can be concluded that the proposed models has high prediction accuracy for the whole cumulative distribution of rainfall and scintillation data.